2000
DOI: 10.1093/ajcn/71.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Dietary influences on bone mass and bone metabolism: further evidence of a positive link between fruit and vegetable consumption and bone health?

Abstract: The BMD results confirm our previous work (but at peripheral bone mass sites), and our findings associating bone resorption with dietary factors provide further evidence of a positive link between fruit and vegetable consumption and bone health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
253
4
7

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 432 publications
(273 citation statements)
references
References 31 publications
9
253
4
7
Order By: Relevance
“…The epidemiological study from the Framingham cohort in elderly men and women, with cross-sectional and longitudinal components, showed positive effects of Mg and K, as part of a diet rich in fruit and vegetables on BMD (Tucker et al, 1999). Similarly, New et al were the first to show in their studies that nutrients rich in fruit and vegetables have beneficial effects on bone, probably due to the alkaline ash these foods create, confirming the hypothesis of the role of bone in acid -base balance regulation (New et al, 1997(New et al, , 2000. Our study, although much smaller and of a cross-sectional nature, is pointing in the same direction.…”
Section: Multiple Regression Resultsmentioning
confidence: 85%
“…The epidemiological study from the Framingham cohort in elderly men and women, with cross-sectional and longitudinal components, showed positive effects of Mg and K, as part of a diet rich in fruit and vegetables on BMD (Tucker et al, 1999). Similarly, New et al were the first to show in their studies that nutrients rich in fruit and vegetables have beneficial effects on bone, probably due to the alkaline ash these foods create, confirming the hypothesis of the role of bone in acid -base balance regulation (New et al, 1997(New et al, , 2000. Our study, although much smaller and of a cross-sectional nature, is pointing in the same direction.…”
Section: Multiple Regression Resultsmentioning
confidence: 85%
“…Some observational studies report that fruit and vegetable consumption is associated with increased bone mineral content (BMC) and BMD 4, 5, 6, 7, 8. Nitrates, present in high concentrations in leafy green and root vegetables, may serve as a dietary component that supports bone health.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Poor nutrition is likely to play a role in the pathogenesis of the disease, and in the last decade, a number of population-based studies have demonstrated a beneficial effect of fruit and vegetables on indices of bone health. (3)(4)(5)(6)(7) There could be several mechanisms by which fruit and vegetables act on bone, either via some pharmacologically active compound found within them or by the base buffering of excess dietary metabolic acids. A recent 2-year randomized, controlled trial found that supplementation with potassium citrate or three additional portions of fruit and vegetables a day did not reduce bone turnover or increase BMD, suggesting that any long-term benefits of fruit and vegetable intake on bone are not due to the provision of alkaline salts.…”
Section: Introductionmentioning
confidence: 99%